Deposition of Pt nanoparticles on different carbonaceous materials by using different preparation methods for PEMFC electrocatalysts - Veizaga, Natalia Soledad (2012)
The objective of this study is to evaluate different methods to obtain Pt (20 wt%)/carbon electrocatalysts, in order to identify the conditions that lead to electrocatalysts with the best electrochemical performance. This paper involves the study of different methods for the deposition and reduction of H2PtCl6 on three carbon supports: Vulcan carbon, Multiwall carbon nanotubes and mesoporous carbons. The depositionereduction methods in liquid phase were carried out with HCOOH or NaBH4 as reducing agents. Besides, the conventional impregnation was carried out by deposition of H2PtCl6 on carbon followed by a reduction with H2 at high temperature. The electrochemical performance of supported Pt catalysts prepared by reduction in liquid phase is strongly dependent on the metallic dispersion, the particle size distribution and the nature of the carbonaceous material used as a support. Results show that the deposition reduction method using HCOOH 0.3 M at 50e60 ºC and a mesoporous carbon leads to the most efficient electrocatalyst.